2002
DOI: 10.1111/j.1532-849x.2002.00234.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of disinfectants on the properties of dental gypsum, part 2: Surface properties

Abstract: Using SEM, 3-dimensional profilometry, and ADA testing methods, we found that the surface roughness of stone casts was adversely affected by using the disinfectant solutions as mixing water substitutes. Gum arabic and calcium hydroxide additives can yield a harder stone surface without compromising other surface properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…Sufficient quality ensures a satisfactory function [22], which in the domain of dental models, represents the fit of the denture, particularly with saw-cut models [23]. The electric profile method with mechanical contact has been shown to be effective for the quantitative evaluation of surface qualities [9,24,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…Sufficient quality ensures a satisfactory function [22], which in the domain of dental models, represents the fit of the denture, particularly with saw-cut models [23]. The electric profile method with mechanical contact has been shown to be effective for the quantitative evaluation of surface qualities [9,24,25,26].…”
Section: Discussionmentioning
confidence: 99%
“…As an essential auxiliary material, dental gypsum has been used for simulating oral cavity models. Put a certain amount of dental gypsum powder and water in a small rubber bowl to knead the gypsum slurry and then cast the slurry into the oral mold to prepare dental restoration, such as an inlay, a crown, a bridge, a partial denture, and a complete denture [2][3][4]. The manufacture of denture model is the basis of denture processing, and the dimensional stability of gypsum is fundamental to achieving a precise fit between dental structure and restorative material [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…These materials include impressions, casts, dental prostheses and appliances, which are often heavily contaminated with microorganisms from saliva and blood. 1 The American Dental Association (ADA) and the Center for Disease Control recommend that the dental impressions and gypsum casts be disinfected before use. 2 Dental stone casts are potentially subject to crosscontamination in prosthodontics because of frequent times exposed to the transfer of infectious agents from blood and saliva to the casts through impressions, record bases and occlusion rims and trial dentures.…”
Section: Introductionmentioning
confidence: 99%
“…A critical study by Stern et al has demonstrated that disinfecting the definitive cast at least seven times from the time of fabrication through insertion of complete or removable partial prostheses is crucial. 3 Two major methods have been proposed to disinfect dental casts, including (1) immersing or spraying the casts with disinfecting solutions, and (2) introducing disinfecting chemicals into gypsum at the time of mixing or using die stone containing disinfectant. 4,5 The immersion of dry casts like gypsum in water or aqueous solutions may be accompanied with the dissolution of sufficient amount of cast material causing a measurable reduction in the dimension of the cast.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation